Financial Innovation and Resilience A Comparative Perspective on the Public Banks of Naples (1462-1808) (Palgrave Studies in the History of Finance,, 2018)
As Ignazio Visco, Governor of the Bank of Italy, says in his Foreword, all economic policy makers today need to re-examine our history to help them confront the challenges of today. This edited volume focuses specifically on the theme of financial innovation and how financial resiliency was achieved in Naples. To highlight both the achievements of the public banks of Naples and their lessons for financial resiliency, the book focuses on financial crises and how they were overcome in Naples in contrast to other European financial systems. The first section focuses on the development of the public banks unique to Naples. The second section compares those with other banking systems and how they responded to the same shock in 1622, caused by the full mobilization of European belligerents to finance their efforts in the Thirty Years War. The next section compares lessons learned in the rest of Europe over the next century and a half. The final section comes back to original start of the narrative arc to suggest ways that today's policymakers and thinkers could use the historical experience of the public banks of Naples to deal better with the ongoing problems stemming from the financial crisis of 2007-08. .